x+(x-6)+2x=74

Simple and best practice solution for x+(x-6)+2x=74 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(x-6)+2x=74 equation:


Simplifying
x + (x + -6) + 2x = 74

Reorder the terms:
x + (-6 + x) + 2x = 74

Remove parenthesis around (-6 + x)
x + -6 + x + 2x = 74

Reorder the terms:
-6 + x + x + 2x = 74

Combine like terms: x + x = 2x
-6 + 2x + 2x = 74

Combine like terms: 2x + 2x = 4x
-6 + 4x = 74

Solving
-6 + 4x = 74

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 4x = 74 + 6

Combine like terms: -6 + 6 = 0
0 + 4x = 74 + 6
4x = 74 + 6

Combine like terms: 74 + 6 = 80
4x = 80

Divide each side by '4'.
x = 20

Simplifying
x = 20

See similar equations:

| (y-3)(y^2-6y+7)= | | 7r^2(3r^2-2r-5)= | | -2(x)=-3x^3-2 | | -7x-1=6x+64 | | 11z+9-3z=-7 | | -3x^3+6m^2+45m=0 | | 35=-5+2x+-7x | | 2(y-6)+20=-4 | | 3x-(x-8)=0 | | ln(3x-2)+ln(x-1)=2ln(x) | | 4r^2+3r-5=0 | | Pc(c-11)+10(5c-3)=3c(c+5)+c(6c-3)-30 | | -8-17n=-14n-6n+31 | | 14x+5=-1 | | (X(2+6i))(X(2-6i))= | | 6.4x+2.8y=2.8y | | y^2+14y+45= | | x^2-10=83 | | 10x+3=-1+11x | | 90+5x=20x-15 | | ln(-2y+5)-ln(y+4)=ln(-11y-2) | | 3.6=2.3x+7.8 | | 700+8x=-34 | | 5(2y-4)=3(4y-4) | | 3(2x+4)=x+47 | | 2x+1=5X-11(4x) | | 5(2x-3)-5=-2(4-2x) | | 4(8-5w)=-2u-4 | | x/4+8=-x-7 | | 14rs+12st-6rt=0 | | X+4.9=-1.1 | | 4(k+7)=-36 |

Equations solver categories